Implementation of the Marriage Dispensation: Exploring the Legal and Social Complexities in Preventing Early Marriage - Putra, Sandio Abid Aurian; Fitriyah, Mas Anienda Tien (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2024)
The Marriage Law has undergone changes as Law No. 16 of 2019 concerning Amendments to Law no. 1 of 1974 concerning Marriage, where previously the minimum age limit for being permitted to enter into marriage was 19 (nineteen) years for men and 16 (sixteen) years for women, now it is 19 (nineteen) years for both men and women . Based on this description, the purpose of this research is to explore the implementation of the granting of a marriage dispensation by the Madiun City Religious Court in reducing underage marriages, after the amendment to the marriage law. This study explores aspects of the implementation of the marriage dispensation as well as the constraints that exist in its application. This research method uses empirical juridical, with a qualitative approach. The results of the research show that the procedure for granting dispensation for marriage at the Madiun City Religious Court is that not everything can be done. There were several applications for dispensation that were actually rejected. The refusal is certainly an attempt to reduce child marriage underage. For example, there are reasons for children who are forced to marry or children who still want to continue their education. The obstacle that occurs in this implementation is that there are parents who are forced to continue their child's marriage. Legal protection for children with this has not been realized properly, given the interests of children who must be sacrificed.